2013
DOI: 10.1080/20742835.2013.11441209
|View full text |Cite
|
Sign up to set email alerts
|

Consensus recommendations for the prevention of cervical cancer in sub-Saharan Africa

Abstract: Cervical cancer is the second most common cancer and the leading cause of cancer-related death in women in sub-Saharan Africa. It is estimated that more than 200 million females older than 15 years are at risk in this region. This paper highlights the current burden of cervical cancer in sub-Saharan Africa, reviews the latest clinical data on primary prevention, outlines challenges in the region, and offers potential solutions to these barriers. Based on these factors, clinical recommendations for the preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…In the present study, we observed that 52.1% of women in age group between 41 and 60 years were diagnosed with SCC, a dominant histomorphological form in invasive cervical cancer [ 12 ]. According to the WHO guidelines, all women between ages of 35–45 years must be screened annually, which can significantly reduce mortality rates [ 27 ]. The degree of differentiation (keratinization) is an important pathological feature in cervical tumors, indicates the site of infection in the cervical mucosal epithelium (squamo-columnar junction) and susceptible to HPV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we observed that 52.1% of women in age group between 41 and 60 years were diagnosed with SCC, a dominant histomorphological form in invasive cervical cancer [ 12 ]. According to the WHO guidelines, all women between ages of 35–45 years must be screened annually, which can significantly reduce mortality rates [ 27 ]. The degree of differentiation (keratinization) is an important pathological feature in cervical tumors, indicates the site of infection in the cervical mucosal epithelium (squamo-columnar junction) and susceptible to HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing cancer related incidence and mortality rates, Sudan is burdened with other public health issues such as malaria, leprosy, tuberculosis, HIV/AIDS thereby causing lack of emphasis and knowledge about this disease [ 40 ]. Thus, introduction of such molecular biomarkers will prove beneficial in early detection and embarking on screening initiatives and reducing mortality [ 27 ]. Recently, WHO has recommended that HPV vaccination should be performed as part of national immunization programs for women between ages 13–26 years to effectively prevent disease [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, cervical cancer ranks as the second most common type of cancer affecting women [2]. In 2012, 266,000 deaths occurred worldwide as a result of cervical cancer, and more than 85% of these deaths occurred in low-and middle-income countries [1].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, 266,000 deaths occurred worldwide as a result of cervical cancer, and more than 85% of these deaths occurred in low-and middle-income countries [1]. In Sub-Saharan Africa, cervical cancer is the leading cause of cancerrelated mortality, with more than 75,000 new cases and over 50,000 deaths reported each year [2]. Human papilloma virus is the leading cause of cervical cancer, with over 70% cases caused by HPV 16 and 18 [3].…”
Section: Introductionmentioning
confidence: 99%
“…An important component of STI management includes partner notification for STIs which aids in interrupting transmission of infections, averting possible re-infection, and preventing STI-related health complications [126]. Partner management (notification and treatment) is a key component of the syndromic management system.…”
Section: Partnership Interventionsmentioning
confidence: 99%